2020
DOI: 10.3390/su12198099
|View full text |Cite
|
Sign up to set email alerts
|

Nursing as a Sustainability Factor of the Health System during the COVID-19 Pandemic: A Qualitative Study

Abstract: Earlier this year, Spain took center stage in the emerging health crisis due to the SARS-CoV-2 pandemic. On 14 March 2020, a state of alarm was declared to manage this health crisis. The contribution of nursing professionals to sustainability of the system during this health crisis has been vital, not only in specialized care but, in a more understated way, in primary care. The objective of the present study was to describe the perceptions and lived experiences of primary care nurses during the COVID-19 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…To avoid this bias, we used recruitment strategies through natural leaders by means of a snowball technique through social media where the target was nursing professionals, highlighting these participants who adequately represented all the strata of the population under study. These same circumstances have been evidenced in similar studies [8,31]. On the other hand, the possibility of non-response due to the self-selection and exclusion of subjects without access to the Internet is currently a problem diminished by the current digital progress and reinforced by the increase in the use of technology in the nursing community.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…To avoid this bias, we used recruitment strategies through natural leaders by means of a snowball technique through social media where the target was nursing professionals, highlighting these participants who adequately represented all the strata of the population under study. These same circumstances have been evidenced in similar studies [8,31]. On the other hand, the possibility of non-response due to the self-selection and exclusion of subjects without access to the Internet is currently a problem diminished by the current digital progress and reinforced by the increase in the use of technology in the nursing community.…”
Section: Methodssupporting
confidence: 54%
“…This must be kept in mind with how Spain is still the leading country in terms of infection rates and how nursing has acquired the role of a retaining wall in the health system [31].…”
Section: Introductionmentioning
confidence: 99%
“…López-Verdugo and colleagues [17] found that this discriminatory vision of the nursing profession derived primarily from the portrayal of the profession in the media, social media, and social information [15]. The value of nursing in society has risen as a result of the response to the COVID-19 pandemic [62,63], but this has not been reflected in nurses' pay nor in the real value or recognition of their professional activity [64].…”
Section: Discussionmentioning
confidence: 99%
“…The findings reflect the need for nursing management and policymakers to develop measures and strategies to ensure appropriate staffing, effective organization, and a supportive work environment [11]. Nurses presented a high degree of satisfaction in the performance of their functions during the pandemic [53].…”
Section: Discussionmentioning
confidence: 65%